Situation of resource allocation in Iranian,s health system - A Rezapoor; F Ebadifard Azar; P Abbasi broujeni (Tehran University of Medical Sciences, 2013)
Background: In order to achieve the goals of health system, trying to evaluate and improve of health system performance via policy and decision makers is necessary.Materials & Methods: This is a descriptive and practical study .Information gathered through sheets through World Health Organization statistical reports. data analyzed by using DEAP software(version of 2) and Data Envelopment Analysis (DEA).Results: Based on study technical efficiency in various scenarios were different. The results showed that health systems are high sensitive to human resources, and health sector's usually share the national expenditure difference scenarios during the period of study which show the managing efficiency and scale improvement s in Iranian health system.Conclusion: This study showed the countries with the highest and lowest performance and efficient states (reference) for the inefficient countries among a few countries which increased their health resources to improve performance. However, with high efficient resource allocations in the most countries to achieve into these results are very significant to economic savings.